A numerical optimization framework for rotor airfoil design - Wilke, G. (My University, 2022)
The design of new helicopter airfoils is a challenging task. The individual blade sections undergo very different flow conditions during the various flight regimes of the helicopter. In forward flight, the advancing side operates in a transonic regime where potentially shock waves can occur, while on the retreating side little flow velocities at high angle of attacks are seen up to reverse flow. In hover, the oncoming tip vortex of the previous blade drastically influences the inflow on the rotor. Therefore, after a brief review of given design techniques, a novel approach for airfoil designs is put forward. A surrogate based multi-objective approach including constraints is utilized to concurrently optimize an airfoil for hover, retreating and advancing side flow, while also enforcing a certain robustness as to not looking at single design points in these global flow regimes. Along with the estimation of design targets, this 2D flow analysis-based framework allowed to optimize the airfoil design of an existing model rotor blade. A comparison over a range of flight conditions of the rotor with and without the new airfoils proved the validity of this approach